Contingency Plans: The Effects of Dependent Coverage Mandate on the Contingent Workforce Decisions of Young Adults - Gibson, Michael. (2018)
Abstract: The majority of Americans obtain their health insurance through their job. However, there is a certain type of employment, contingent work, that does not offer health insurance. These jobs are characterized by a lack of relationship between the employer and worker. In 2010, the Dependent Coverage Mandate was passed, allowing young adults to remain on their parents' employer provided health insurance until age 26. This law broke the link between employment and health insurance for young adults and so in theory could have freed young adults to take up more contingent work. Using a difference in difference analysis, this paper will show that the DCM caused a 0.31 percentage point increase in the number of young men aged 23-25 who take up contingent work, an increase of roughly 38.7% of the mean percentage of 23-25-year-old men doing contingent work in the pre-treatment period.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Economics.; Advisors: David Garman, and Melissa McInerney.; Keywords: Labor economics, Economics, and Public policy.